Accounting Choice for Intangible Assets in Indonesia’s Entertainment and Media Entities - I'ana Umma; Piscabrian Boeny Saputra; Muhammad Ubaidillah; Muhammad Wildan Sholih (Fakultas Ekonomi dan Bisnis, Universitas Muhammadiyah Cirebon, 2024)
A good understanding of the management and reporting of intangible assets is one of the efforts made by the entity to maintain its reputation, financial performance, and the trust of investors and stakeholders. The existence of gaps in accounting practices causes the emergence of differences in managers’ behaviour in preparing financial statements. This is what makes the income strategy related to intangible assets can be informative or opportunistic. By analyzing factors such as entity size, leverage, and sales compensation, this study aims to examine whether these strategies are informative or opportunistic. This study is a cross-sectional and time-series study with a quantitative design. The data collected were taken from the Annual Report of Entity of Entertainment and Media listed on the IDX with a period of 2021-2022. The size of the entity has a significant effect on income strategies that shows intangible assets reporting tends to be conservative by presenting informatively. Meanwhile, highly leveraged entities are more likely to adopt aggressive strategies; in other words, leverage influences opportunist behaviour in expressing income strategies regarding intangible assets. The impact of sales compensation on financial managers' income strategies for intangible assets is not consistent and can be influenced by various factors.